Ruang Lingkup Asesmen Pembelajaran SD/MI (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Learning assessment at the primary school and madrasah level plays an important role in supporting a holistic education process. This study aims to explore teachers' understanding of formative and authentic assessments and the challenges they face in implementing them. Data shows that around 60% of teachers still rely on written test-based summative assessments, which tend to measure limited cognitive abilities and can cause stress in students. Using a qualitative approach with a case study method, this research involved interviews with teachers and analysis of learning documents. Results show that teachers' understanding of formative and authentic assessments greatly affects the effectiveness of their implementation. Teachers who understand the importance of formative assessment are better able to provide constructive feedback, while an understanding of authentic assessment allows them to design tasks that are relevant to the real context. Challenges such as limited training and the habit of using traditional methods are still obstacles. This study recommends the need for continuous training for teachers to improve their understanding and skills in designing more diverse and effective assessments. Thus, it is expected that assessments can create more engaging learning experiences and support students' holistic development.